A model of dynamical system for the attainment of consensus - Satur, O. R.; Kharchenko, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.9 + 316.4 We propose a mathematical model for the diffusion of opinions, which eventually lead to the attainment of the state of consensus. The theory of conflict dynamical systems with attractive interaction is used for the construction of the model. The behavior of the model in the case of making binary decisions is described in detail and the behavior of trajectories in the decision-making model with many alternative positions is investigated.